Evanescent Wave Fiber Optic Sensor for Detection of Fe+2 Using LED Source - Kulkarni, Vijay K.; Bendigeri, Harish H. (Advanced Aspects of Engineering Research Vol. 16, 2021)
A cost effective and sensitive chemical sensor is developed for detection ofFe+2 based on evanescent wave fiber optic absorption technique. A high quality LED source is used in sensing mechanism. Multimode sensor grade plastic clad silica (PCS) fiber is adopted as sensing arm, whose centre cladding region is taken out to interact with the surrounding region(Fe+2 ions).This unclad region of the PCS fiber is used as a sensing element in this experiment. The sensor developed is highly sensitive over the dynamic range of concentration from 0.1ppm to 100ppm for the detection of Fe+2 in water.